Whole-genome sequencing and phylogenetic analysis capture the emergence of a multi-drug resistant Salmonella enterica serovar Infantis clone from diagnostic animal samples in the United States - Srednik, Mariela E.; Morningstar-Shaw, Brenda R.; Hicks, Jessica A.; Tong, Christopher; Mackie, Tonya A.; Schlater, Linda K. (Frontiers in Microbiology, 2023)
Salmonella enterica is a major cause of foodborne illness in the United States. A multi-drug resistant (MDR) emergent Salmonella Infantis (ESI) with a megaplasmid (pESI) was first identified in Israel and Italy and subsequently reported worldwide. The ESI clone carrying an extended spectrum β-lactamase blaCTX-M-65 on a pESI-like plasmid and a mutation in the gyrA gene has recently been found in the United States in poultry meat. We analyzed the phenotypic and genotypic antimicrobial resistance, genomics and phylogeny of 200 S. Infantis isolates from animal diagnostic samples. Of these, 33.5% were resistant to at least one antimicrobial and 19.5% were multi-drug resistant (MDR). Eleven isolates from different animal sources were phenotypically and genetically similar to the ESI clone. These isolates had a D87Y mutation in the gyrA gene conferring reduced susceptibility to ciprofloxacin and harbored a combination of 6 - 10 resistance genes: blaCTX-M-65, aac(3)-IVa, aadA1, aph(4)-Ia, aph(3')-Ia, floR, sul1, dfrA14, tetA, fosA. These eleven isolates carried class I and class II integrons and three virulence genes: sinH, involved in adhesion and invasion, ybtQ and ybtP, associated with iron transport. These isolates were also closely related to each other (separated by 7 to 27 SNPs) and phylogenetically related to the ESI clone recently found in the U.S. This dataset captured the emergence of the MDR ESI clone in multiple animal species and the first report of a pESI-like plasmid in isolates from horses in the U.S.